Intrahousehold dynamics in South Asia: Understanding the relationships between women's empowerment, task sharing, decision making, and diets among women - Kumar, Neha; Quisumbing, Agnes R.; Manohar, Swetha; Banerjee, Archis; Gupta, Shivani; Chauhan, Alka; Patwardhan, Sharvari; Koirala, Uma (MedRxiv, 2025)
Despite the growing evidence on the role of women in agriculture and nutrition, interlinkages between empowerment among women, gendered task allocation, and nutrition are rarely studied together. Using data from the Transforming Agrifood Systems in South Asia (TAFSSA), a household survey that used a plate-to-farm assessment approach in three countries (Bangladesh, India and Nepal), the paper investigates the associations between empowerment of women, gendered task allocation, decision-making among women, and diets among women. Our findings reveal complex and context-specific differences in associations between task allocation, decision-making and empowerment among. While agency in decision-making among women is positively associated with empowerment in all three country contexts, associations between gendered task allocation and empowerment vary. The share of tasks performed by females, particularly in agriculture and food preparation) is positively associated with empowerment among women, but the proportion of tasks shared equally between males and females does not necessarily empower women. Gendered task allocation and empowerment among women are not significantly associated with diets of women in the three countries, owing to the greater importance of broader socio-economic and context-specific factors such as wealth, education, and regional factors in explaining the variance in dietary outcomes. These findings highlight the need to take a holistic approach that addresses gender norms and household resource constraints to improving empowerment of women, while also addressing local accessibility/availability of nutritious foods to enhance the quality of diets of women.